(untitled) (Issues in Social and Environmental Accounting (ISEA), 2010)
The new millennium saw the emergence of a new way of thinking about the func tions and duties of modern corporations. The growing international demands for companies to be more transparent and accountable for their economic, social and environmental impacts everywhere they operate. Corporate managers are pressed with more responsibility to serve the needs of society at large. Today, businesses are expected not only to in crease their bottom line but also to oper ate within the ‘new moral marketplace’. Corporate morality is increasingly being judged by consumers, investors and em ployees. Terms that are alien to many a few years ago such as ‘green marketing’, ‘environmentally friendly’, ‘gender sen sitive’, ‘fair trade’, ‘against animal test ing’ and many more become household words and high on consumers’ con science of today. Beyond that, global issues like, the oil crisis, environmental degradation, human rights, labour issues and energy issue forced the companies to reconsider their objectives. Instead of just trying to maximize profit and please their shareholders, many multinational corporations are beginning to understand that they now have a broad spectrum of stakeholders. This includes investors, creditors, employee, governments, NGOs and the various communities in which they operate. Businesses have to satisfy all these stakeholders’ needs, thus have an additional role and purpose. Hence, the term corporate social respon sibility (CSR) was born.